Smart contracts as an efficient solution to the consumer’s distrust of e-commerce - Monsante Moy, Isabella (2021)
The exponential growth of e-commerce in Peru has generated new problems in the effectiveness of consumer rights and the consequent consumer distrust in e-commerce transactions. Government authorities have repeatedly mentioned that a solution to these problems would be the regulation of electronic consumer’s relationships established at national level. This solution goes on the same page with the tendency of the European Union to regulate digital markets. However, is the legislative initiative an ideal solution to solve the new problems generated by e-commerce?.In this article, the authors find that regulation of e-commerce would not completely solve the new problems generated by it. They evidence the necessity of utilizing market solutions based on new technological mechanisms such as smart contracts. These tools, together with the incentive of the authorities that protect consumers’ rights, will be able to efficiently solve the new problems that are generated in this new decade.